Exploring the downside of open knowledge resources: The case of indigenous knowledge systems and practices in the Philippines - Alexander Gonzalez Flor (Open Praxis, 2013)
The paper is based on the challenges encountered by the researcher while conducting a study titled “Design, Development and Testing of an Indigenous Knowledge Management System Using Mobile Device Video Capture and Web 2.0 Protocols.” During the conduct of the study the researcher observed a marked reluctance from organized indigenous people’s groups to participate in the initiative. It soon became apparent that interfacing indigenous knowledge with open access concepts held complicated issues. The inhibiting factors enumerated and discussed in the paper deal with: honoring indigenous belief systems; respecting the privacy of indigenous peoples; dealing with indigenous knowledge system (IKS) protocols; the significance of context in IKS; mainstream prejudice and value judgments among non-indigenous people users; and the misrepresentation of indigenous knowledge.